2019
DOI: 10.1186/s12902-019-0373-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing for type 1 diabetes autoantibodies in gestational diabetes mellitus (GDM): is it clinically useful?

Abstract: Gestational Diabetes Mellitus (GDM) is the most common metabolic disorder in pregnancy, and it is associated with increased risk of morbidity in maternal-fetal outcomes. GDM is also associated with a higher risk to develop diabetes in the future. Diabetes-related autoantibodies (AABs) have been detected in a small percentage (usually less than 10%) of women with gestational diabetes. The prevalence in gestational diabetes of these autoimmune markers of type 1 diabetes (T1D) has been assessed in many studies, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 62 publications
2
23
0
Order By: Relevance
“…Additionally, recent data have shown that in a subgroup of GDM patients (<10%), intolerance to carbohydrate is associated with autoimmunity against β‐cells. In this subgroup, the risk of progression to T1DM and/or LADA after pregnancy is higher …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent data have shown that in a subgroup of GDM patients (<10%), intolerance to carbohydrate is associated with autoimmunity against β‐cells. In this subgroup, the risk of progression to T1DM and/or LADA after pregnancy is higher …”
Section: Resultsmentioning
confidence: 99%
“…In this subgroup, the risk of progression to T1DM and/or LADA after pregnancy is higher. 56 Contrasting to mediators, the profile of immune cells has received less attention. This review presents a brief overview of the studies published in the last decade which analysed immune cells both in PB and in placenta of GDM and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“… Consistent with nonautoimmune initiation of T1D, both subjects with MODY and subjects with gestational diabetes mellitus, during growth phases, with common detrimental HLA haplotypes or other T1D risk variants, can first develop apoptotic and then immune forms of cell death associated with autoantibodies secondary to nonimmunogenic MODY mutations. Early apoptotic cell death near puberty or during gestation could lead to clinical phenotypes similar to autoimmune diabetes, even mistaken for T1D ( 71 , 72 ). T2D risk variants of TCF7L2 are associated with accelerated conversion from single (insulin autoantibody or IA-2 antigen) to multiple autoantibodies in the context of increased BMI in children, thereby increasing T1D risk ( Supplementary Material, part 5 ) ( 73 ).…”
Section: Genetic Implicationsmentioning
confidence: 99%
“…Some GDM women present analogies with type 1 DM. Autoantibody positivity, especially glutamic acid decarboxylase antibodies (GADA), might be found in less than 10% of GDM cases (Incani, Baroni, & Cossu, ; Lapolla, Dalfra, & Fedele, ). It is difficult to precisely estimate the value of autoantibody positivity (Incani et al., ).…”
Section: Genetics Of Gestational Diabetes Mellitusmentioning
confidence: 99%
“…Autoantibody positivity, especially glutamic acid decarboxylase antibodies (GADA), might be found in less than 10% of GDM cases (Incani, Baroni, & Cossu, ; Lapolla, Dalfra, & Fedele, ). It is difficult to precisely estimate the value of autoantibody positivity (Incani et al., ). However, it was found that positive autoantibodies are positively correlated with risk of type 1 DM in the future (Fuchtenbusch, Ferber, Standl, & Ziegler, ).…”
Section: Genetics Of Gestational Diabetes Mellitusmentioning
confidence: 99%